Collection : U.S. architecture - Galindo, Michelle, ....- ([s.l.] : Braun Publishing, 2009)
American architecture has created a symbol for itself in the skyscraper. It is a typology that seems to shout Yes we can!, and the superpower lives by these words to this day. As a little boy, President Barack Obama dreamed of becoming an ar-chitect. Now, those who have fulfilled this dream demonstrate how architecture in the USA has moved on past the skyscraper. The generously illustrated volume from the trilingual Collection series reflects the complete bandwidth of the architecture of this vast nation. Top contemporary projects completed in the last few years have been selected, representing many different categories, including residential houses, office buildings and government buildings as well as sports facilities, research laboratories and museums.
Dreitalig : Engels - Frans - Duits
Keywords: Architectuur ; Verenigde Staten